Calculation and modeling of seasonally freezing soils of the road highway in the area of Kosshy (Astana, Kazakhstan) in Frost 3D program - Sarsembayeva, A.S.; Zhussupbekov, A.Zh.; Wang, D.W.; Mussakhanova, S.T.; Omarov, A.R. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
This article simulates ground conditions on a road section near Kosshy settlement (Astana, Kazakhstan) using Frost 3D modeling program. This program is used in scientific and engineering projects to assess the impact of climate change on frozen soils and engineering structures built on them. This program allowed to perform a thermal forecast for a section of road pavement, which is located in the third climatic zone, where the soil is saturated with moisture and has a high filtration rate. A three-dimensional model of the design area was also developed, taking into account the terrain and geological and lithological structure of the soil. This software complex allows to receive scientifically grounded forecasts of thermal regimes of permafrost soils under conditions of thermal impact of pipelines, production wells, hydraulic and other structures taking into account thermal stabilization of the ground. In this work we applied the program capabilities for seasonally freezing soils of Astana. Modeling in the program Frost 3D Universal allowed us to simulate and predict heat and mass transfer in the ground, as it can affect the service life of the road surface. The soil bases of highways as well as pavement layers remain in a stable frozen state during short-term temperature increases up to +6.6 °C and have a sufficient safety margin. When the air temperature rises for a short period of time, only 25 cm of the upper part of the pavement is exposed, which corresponds to the top layer of the hot highly porous asphalt concrete mix base.